Influence of microgravity on physiological and biochemical transformation of orchids different morphoecotypes - Cherevchenko, T.M.; Zaimenko, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Negative influence of long-term clinostation on the orchids growth processes has been shown. The negligible growth simulation was observed after 30-day cultivation. The analogous dependnce was observed when chlorophyll's contains in leaves of orchids was analyzed. Clinostation causes increase of free amino acids number compared with the control. Macro- and microelements in the orchids vegetative organs also changed considerably. Biochemical content of orchids with different morphological structure was examined under the conditions of hermetically sealed cabin. It was determined that photosynthetic pigment content increased and free amino acids quantity decreased.